If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15ab + 2a = 0 Reorder the terms: 2a + 15ab = 0 Solving 2a + 15ab = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), 'a'. a(2 + 15b) = 0Subproblem 1
Set the factor 'a' equal to zero and attempt to solve: Simplifying a = 0 Solving a = 0 Move all terms containing a to the left, all other terms to the right. Simplifying a = 0Subproblem 2
Set the factor '(2 + 15b)' equal to zero and attempt to solve: Simplifying 2 + 15b = 0 Solving 2 + 15b = 0 Move all terms containing a to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 15b = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 15b = 0 + -2 15b = 0 + -2 Combine like terms: 0 + -2 = -2 15b = -2 Add '-15b' to each side of the equation. 15b + -15b = -2 + -15b Combine like terms: 15b + -15b = 0 0 = -2 + -15b Simplifying 0 = -2 + -15b The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
a = {0}
| 2+3*5-8= | | 13x-7.(x-2)=44 | | 9x^2-4= | | 2x+4(16+x)=40 | | 6-x=3 | | 5+8x=20+2x | | 8(2t+1)=4(7t+7) | | 2x+4(16-x)=40 | | 0.075(x+2000)=0.08x+0.06(2000) | | X^2-36= | | .3x+.12=3.72 | | 3x-6y-2=16 | | 3t^2-48t+180=0 | | 9-26x=36 | | y-6=-25 | | 1/7(3y+2)=2+1/3(y+2) | | 3x-6y+2=16 | | 3y-6x+2=16 | | 5(x-3)=-40 | | -26-15x=19 | | 5x^2+2x-9=0 | | 2x=3x+5+865 | | -15x-26=19 | | (7z-3)(z+5)-(7z-3)(z-4)= | | 5t-2t=16 | | x*5+250=x*15-10 | | 4=18+x | | 14x+18=-10 | | 0.5(x^2+8x)= | | 4(x-5)=4x-5 | | 5x+4=3[2x-1] | | -5x-6=16 |